Self-Care Management Penderita Hipertensi - Moch Rivan Muharam; Dede Suharta Dede Suharta; Hasbi Taubah Ramdani; Tantri Puspita; Wahyudin (LPPM STIKES Mataram, 2024)
Introduction: High blood pressure is a global health problem that requires significant attention because it is the main cause of death and increasing. This disease causes high morbidity and mortality rates, and it can also lead to complications such as heart disease, kidney failure, and stroke. Patients with high blood pressure often behave poorly and do not comply with antihypertensive therapy due to the influence of values and client trust. Objective: This study aims to understand the selfcare management picture among hypertensive patients at Cisewu Health Center in 2023. Method: This study uses a descriptive quantitative method with a sample size of 78 respondents, using the Slovin formula. Data collection was done using questionnaires, and statistical analysis was conducted univariately. Results: Some respondents have poor diets, physical exercise, medication intake, blood pressure monitoring, and smoking cessation efforts. Conclusion: This study is a description of the management of splinting for fracture patients in the ER at Kayangan Health Center, North Lombok Regency. 76.9% of respondents carried out according to the SOP.